Aluminum alloy for new energy automobile and preparation method of aluminum alloy

By using specific proportions and preparation methods of Cu, Mg, Zn and TiB2 in aluminum alloys, the problem that aluminum alloys are difficult to have both strength, elastic modulus and high-temperature performance when there are fewer alloy elements, and the problem is solved. Applications in the field of automobile manufacturing have improved the comprehensive performance of aluminum alloys.

CN119194186APending Publication Date: 2024-12-27LIAONING ZHONGWANG GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411316118.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

When existing aluminum alloys improve strength, elastic modulus and high temperature performance, it is difficult to have excellent performance under the conditions of fewer alloy elements, and their applications in the field of automobile manufacturing are limited.

Method used

Using the specific weight ratio of Cu, Mg, Zn and TiB2, an aluminum alloy is prepared by preparation methods such as primary remelting, homogenizing heat treatment, extrusion and solution treatment to ensure the appropriate distribution and uniformity of TiB2 particles in the alloy. to improve the mechanical properties and high temperature properties of aluminum alloys.

Benefits of technology

With less introduction of alloy metals, the strength, yield strength, tensile strength, elongation and elastic modulus of aluminum alloys are significantly improved, meeting the performance requirements in the field of automobile manufacturing and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194186A_ABST
    Figure CN119194186A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum alloy processing, in particular to an aluminum alloy for a new energy automobile and a preparation method thereof. The aluminum alloy comprises the following components in percentage by weight: 1.2 to 2.8 percent of Cu; the content of Mg is 2.1 to 3.8 percent; the content of Zn is 5.1 to 8.1 percent; the content of TiB2 is 0.5 to 2 percent; the total content of other impurity elements is less than or equal to 0.05%; and the balance of Al. The aluminum alloy has excellent high-temperature performance, mechanical performance and elastic modulus while containing low-content alloy metal. And the comprehensive performance of the aluminum alloy can be further improved by adopting the specific preparation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aluminum alloy processing, and specifically relates to an aluminum alloy for new energy vehicles and a preparation method thereof. Background Art

[0002] In recent years, particle-reinforced aluminum-based composites have been increasingly used worldwide, and are increasingly widely used in industries such as aviation, aerospace, and transportation. Particle-reinforced aluminum-based composites are aluminum-based composites with hard particles as the reinforcement phase. Among the many reinforcement phase particles, hard particles have excellent strength, which can overcome the deficiencies of some weak properties of the aluminum matrix, making the composite material have the advantages of both. In aluminum-based composites, TiB 2 Particle reinforcement mainly plays the role of improving mechanical properties such as hardness, wear resistance, strength, etc., and can also resist high temperatures. The improvement of this performance has broadened the application of aluminum alloys in automobiles. Therefore, it is generally required that the reinforcement phase has excellent high temperature performance in addition to high strength and elastic modulus.

[0003] At present, the existing technology adopts the preparation of aluminum alloys by adding multiple metals and reinforcing phases, such as Si, Ni, Zr, etc. Although aluminum alloys with excellent performance can be obtained, in actual production, it is necessary to add as little metal and reinforcing phase as possible to aluminum alloy materials, which can meet the performance requirements of aluminum alloys and reduce production costs, and then be used in the field of automobile manufacturing.

[0004] In summary, it is urgent to solve the problem that the existing technology has few alloy elements and it is difficult for aluminum alloys to have excellent strength, elastic modulus and high temperature performance. Summary of the invention

[0005] The present invention aims to solve the technical problem that aluminum alloys use less alloying elements but are difficult to have excellent strength, elastic modulus and high temperature performance.

[0006] In order to achieve the above object, the first aspect of the present invention provides an aluminum alloy, wherein the components and their weight percentages in the aluminum alloy are:

[0007] Cu content is 1.2-2.8%;

[0008] Mg content is 2.1-3.8%;

[0009] Zn content is 5.1-8.1%;

[0010] TiB 2 The content is 0.5-2%;

[0011] The total content of other impurity elements is ≤0.05%;

[0012] The balance is Al.

[0013] A second aspect of the present invention provides a method for preparing the above aluminum alloy, wherein the preparation method comprises the following steps:

[0014] The aluminum alloy raw materials are placed in a crucible for melting and casting.

[0015] Carry out a remelting, refining, slagging and casting;

[0016] The aluminum alloy ingot after one remelting and casting is subjected to homogenization heat treatment, and the homogenization system adopts (380-400℃)×3h+(410-440℃)×(8-16h)+(450-480℃)×(20-28h);

[0017] The aluminum alloy ingot after homogenization heat treatment is extruded, the extrusion die temperature is 410-430°C, the aluminum alloy casting rod heating temperature is 425-440°C, and the extrusion speed is 0.5-1m / min;

[0018] The extruded aluminum alloy bar is subjected to a solid solution treatment at a temperature of 455-465°C × (60-100) min;

[0019] The aluminum alloy rod after solid solution is subjected to thermal insulation aging, adopting a double-stage aging system, (140-160℃)×(8-12h)+(80-120℃)×(8-12h), and water cooling.

[0020] A third aspect of the present invention provides application of the above aluminum alloy or the aluminum alloy prepared by the above preparation method in the automotive field.

[0021] The beneficial effects of the present invention are:

[0022] (1) In the aluminum alloy provided by the present invention, when less alloy metal is introduced, the specific TiB 2 The content can enhance the strength of aluminum alloys, and can be further enhanced by combining with other alloy metals with specific contents;

[0023] (2) The preparation method provided by the present invention adopts one-time remelting and a specific and reasonable homogenization system to improve the high-temperature performance of the aluminum alloy, while having excellent yield strength, tensile strength, elongation and elastic modulus. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A comparison diagram of the homogenization system in the preparation method of the present invention and the traditional homogenization system;

[0025] Figure 2 is the microstructure diagram of Example 8;

[0026] Figure 3 It is the microstructure diagram of comparative example 5;

[0027] Figure 4 It is the microstructure diagram of Comparative Example 6;

[0028] Figure 5 is the SEM image of Example 4;

[0029] Figure 6 This is the SEM image of Comparative Example 2. DETAILED DESCRIPTION

[0030] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0031] In order to improve the comprehensive performance of aluminum alloys, the existing technology adopts the method of increasing the alloy metal composition and content. Although it can improve the performance of aluminum alloys, it is difficult to apply in actual production, let alone in automobile manufacturing. The inventors found that when only Cu, Mg, Zn and the reinforcing phase TiB 2 , with a specific weight ratio and a specific preparation method, the aluminum alloy has a low alloy metal content and has excellent high temperature properties, mechanical properties and elastic modulus.

[0032] To this end, the first aspect of the present invention provides an aluminum alloy, wherein the components and their weight percentages in the aluminum alloy are:

[0033] Cu content is 1.2-2.8%;

[0034] Mg content is 2.1-3.8%;

[0035] Zn content is 5.1-8.1%;

[0036] TiB 2 The content is 0.5-2%;

[0037] The total content of other impurity elements is ≤0.05%;

[0038] The balance is Al.

[0039] In the present invention, the inventors found that when a small amount of alloy metal is introduced, an appropriate amount of TiB2 particles is added to the aluminum alloy, which can cause fine grain strengthening and dispersion strengthening of the material, and cooperate with the specific alloy metal component content to improve the comprehensive performance of the aluminum alloy obtained; excessive TiB2 will increase the internal defects of the composite material and affect the quality of the cast rod; a small amount of TiB2 will aggravate the agglomeration phenomenon during the casting process, and the refinement effect will be weakened, which is not conducive to the improvement of performance; therefore, the addition of an appropriate amount of TiB2 particles will cause the grains of the alloy material to begin to become significantly smaller. It will also be dispersed in the aluminum alloy matrix in the form of very fine particles, enhancing the barrier effect of relative dislocations and thus improving the strength of the alloy.

[0040] According to some preferred embodiments of the present invention, the components in the aluminum alloy and their weight percentages are:

[0041] Cu content is 1.2-2%;

[0042] Mg content is 2.1-2.9%;

[0043] Zn content is 5.1-6.1%;

[0044] TiB 2 The content is 0.5%-2%;

[0045] The total content of other impurity elements is ≤0.05%;

[0046] The balance is Al.

[0047] In the present invention, the aluminum alloy prepared from the above components has better comprehensive properties.

[0048] A second aspect of the present invention provides a method for preparing the above aluminum alloy, wherein the preparation method comprises the following steps:

[0049] The aluminum alloy raw material is placed in a crucible for melting and casting, and stirred with a stirrer for 5-10 minutes. The obtained cast rod is remelted at 720-740°C, refined, slag-stripped, and cast;

[0050] The aluminum alloy ingot after one remelting and casting is subjected to homogenization heat treatment, and the homogenization system adopts (380-400℃)×3h+(410-440℃)×(8-16h)+(450-480℃)×(20-28h);

[0051] The aluminum alloy ingot after homogenization heat treatment is extruded, the extrusion die temperature is 410-430°C, the aluminum alloy casting rod heating temperature is 425-440°C, and the extrusion speed is 0.5-1m / min;

[0052] The extruded aluminum alloy bar is subjected to a solid solution treatment at a temperature of 455-465°C × (60-100) min;

[0053] The aluminum alloy rod after solid solution is subjected to thermal insulation aging, adopting a double-stage aging system, (140-160℃)×(8-12h)+(80-120℃)×(8-12h), and water cooling.

[0054] In the present invention, the inventors found that remelting can change the aggregation degree of cast rods after casting, discharge residual molten salt in the melt, and improve the mechanical properties of the alloy. According to the analysis of the alloy homogenization annealing principle, in order to improve production efficiency and shorten the homogenization time, the most important thing is to increase the homogenization annealing temperature. Considering the complex composition of the alloy, high homogenization annealing temperature is prone to overburning at the component segregation position, resulting in thermal cracks and causing the ingot to be scrapped. Multi-stage homogenization can take into account both requirements.

[0055] Furthermore, the inventors unexpectedly discovered that the aluminum alloy described in the first aspect of the present invention, prepared by the preparation method described in the present invention, has better mechanical properties and high-temperature properties.

[0056] According to the present invention, the aluminum alloy raw materials include pure Al, Al-Cu alloy, zinc ingot, magnesium ingot, KBF 4 and K 2 TiF 6 .

[0057] According to the present invention, the smelting and casting step comprises the following steps:

[0058] Put pure Al, Al-Cu alloy and zinc ingot into a graphite crucible and heat them in a resistance furnace at 850℃ until they are melted; after melting, when the temperature is ≥730℃, add magnesium ingot; wait for the intermediate alloy to be completely melted and stir it thoroughly; add mixed salt and stir it thoroughly with a graphite stirrer to remove the slag, and put Al 2 O 3 , dilute the reaction water and keep warm for 10 minutes; after keeping warm, add a certain amount of pure Al.

[0059] According to the present invention, the KBF 4 and K 2 TiF 6 Preparation of TiB by in-situ reaction 2 ;

[0060] According to the present invention, the in-situ reaction temperature is (850±3)°C.

[0061] In the present invention, the inventors found that as the temperature increases, the time required for the melt components to fully react will be greatly shortened. However, since the aluminum alloy solution has severe gas absorption at high temperatures, resulting in deterioration of the solution quality, the above-mentioned in-situ reaction temperature is selected.

[0062] A third aspect of the present invention provides application of the above aluminum alloy or the aluminum alloy prepared by the above preparation method in the automotive field.

[0063] Test Method

[0064] The yield strength is measured according to GB / T228.1-2021;

[0065] The tensile strength is measured according to GB / T228.1-2021;

[0066] The elongation is measured according to GB / T228.1-2021;

[0067] The elastic modulus is measured according to GB / T228.1-2021;

[0068] High temperature performance is measured according to GB / T228.2-2010.

[0069] The technical scheme of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Obviously, the embodiments described herein are only some embodiments of the present invention and are not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments implemented by ordinary technicians in this field without making creative improvements belong to the protection scope of the present invention.

[0070] Embodiment 1:

[0071] Pure Al, Al-Cu alloy, zinc ingot, magnesium ingot, KBF 4 , K 2 TiF 6 and Al 2 O 3 As raw materials, cast in a conventional crucible melting furnace, fully stirred with a graphite stirrer, remelted at 750°C, homogenized at 390°C × 3h + 440°C × 12h + 465°C × 24h, extrusion die temperature at 420°C, aluminum alloy casting heating temperature at 435°C, solution system at 460°C × 70min, insulation aging at 150°C × 10h + 100°C × 10h, water cooling. The components and weight percentages (wt%) of the aluminum alloy are Cu: 2.8, Mg: 3.8, Zn: 5.1, TiB 2 :0.5%; the total content of other impurity elements ≤0.05%, the balance is Al.

[0072] Embodiment 2:

[0073] Pure Al, Al-Cu alloy, zinc ingot, magnesium ingot, KBF 4 , K 2 TiF 6 and Al2 O 3 As raw materials, cast in a conventional crucible melting furnace, fully stirred with a graphite stirrer, and remelted at 750°C. The homogenization system is 380°C×3h+440°C×12h+465°C×24h, the extrusion die temperature is 420°C, the aluminum alloy casting temperature is 435°C, the solid solution system is 460°C×70min, the insulation aging is 150°C×10h+100°C×10h, and water cooling. The components and their weight percentages (wt%) of the obtained aluminum alloy are Cu: 2.8, Mg: 3.8, Zn: 5.1, TiB 2 : 1%; the total content of other impurity elements is ≤0.05%, and the balance is Al.

[0074] Example 3

[0075] Pure Al, Al-Cu alloy, zinc ingot, magnesium ingot, KBF 4 , K 2 TiF 6 and Al 2 O 3 As raw materials, cast in a conventional crucible melting furnace, fully stirred with a graphite stirrer, remelted at 750°C, homogenized at 390°C × 3h + 440°C × 12h + 465°C × 24h, extrusion die temperature at 420°C, aluminum alloy casting heating temperature at 435°C, solution system at 460°C × 70min, insulation aging at 150°C × 10h + 100°C × 10h, water cooling. The components and weight percentages (wt%) of the aluminum alloy are Cu: 2.8, Mg: 3.8, Zn: 5.1, TiB 2 : 1.5%; the total content of other impurity elements is ≤0.05%, and the balance is Al.

[0076] Example 4

[0077] Pure Al, Al-Cu alloy, zinc ingot, magnesium ingot, KBF 4 , K 2 TiF 6 and Al 2 O 3 As raw materials, cast in a conventional crucible melting furnace, fully stirred with a graphite stirrer, remelted at 750°C, homogenized at 390°C × 3h + 440°C × 12h + 465°C × 24h, extrusion die temperature at 420°C, aluminum alloy casting heating temperature at 435°C, solution system at 460°C × 70min, insulation aging at 150°C × 10h + 100°C × 10h, water cooling. The components and weight percentages (wt%) of the aluminum alloy are Cu: 2.8, Mg: 3.8, Zn: 5.1, TiB 2: 2%; the total content of other impurity elements is ≤0.05%, and the balance is Al.

[0078] Example 5

[0079] Pure Al, Al-Cu alloy, zinc ingot, magnesium ingot, KBF 4 , K 2 TiF 6 and Al 2 O 3 The raw material is cast in a conventional crucible melting furnace, fully stirred with a graphite stirrer, and the prepared cast rod is remelted at 750°C. The homogenization system is 390°C×3h+440°C×12h+465°C×24h, the extrusion die temperature is 420°C, the aluminum alloy cast rod heating temperature is 435°C, the solid solution system is 460°C×70min, the insulation aging is 150°C×10h+100°C×10h, and water cooling. The components and their weight percentages (wt%) of the obtained aluminum alloy are Cu: 2, Mg: 2.9, Zn: 6.1, TiB 2 :0.5%; the total content of other impurity elements ≤0.05%, the balance is Al.

[0080] Example 6

[0081] Pure Al, Al-Cu alloy, zinc ingot, magnesium ingot, KBF 4 , K 2 TiF 6 and Al 2 O 3 The raw material is cast in a conventional crucible melting furnace, fully stirred with a graphite stirrer, and the prepared cast rod is remelted at 750°C. The homogenization system is 390°C×3h+440°C×12h+465°C×24h, the extrusion die temperature is 420°C, the aluminum alloy cast rod heating temperature is 435°C, the solid solution system is 460°C×70min, the insulation aging is 150°C×10h+100°C×10h, and water cooling. The components and their weight percentages (wt%) of the obtained aluminum alloy are Cu: 2, Mg: 2.9, Zn: 6.1, TiB 2 : 2%; the total content of other impurity elements is ≤0.05%, and the balance is Al.

[0082] Example 7

[0083] Pure Al, Al-Cu alloy, zinc ingot, magnesium ingot, KBF 4 , K 2 TiF 6 and Al 2 O 3As raw materials, cast in a conventional crucible melting furnace, fully stirred with a graphite stirrer, remelted at 750°C, homogenized at 390°C × 3h + 440°C × 12h + 465°C × 24h, extrusion die temperature at 420°C, aluminum alloy casting heating temperature at 435°C, solution system at 460°C × 70min, insulation aging at 150°C × 10h + 100°C × 10h, water cooling. The components and weight percentages (wt%) of the aluminum alloy obtained are Cu: 1.2, Mg: 2.1, Zn: 8.1, TiB 2 :0.5%; the total content of other impurity elements ≤0.05%, the balance is Al.

[0084] Example 8

[0085] Pure Al, Al-Cu alloy, zinc ingot, magnesium ingot, KBF 4 , K 2 TiF 6 and Al 2 O 3 As raw materials, cast in a conventional crucible melting furnace, fully stirred with a graphite stirrer, remelted at 750°C, homogenized at 390°C × 3h + 440°C × 12h + 465°C × 24h, extrusion die temperature at 420°C, aluminum alloy casting heating temperature at 435°C, solution system at 460°C × 70min, insulation aging at 150°C × 10h + 100°C × 10h, water cooling. The components and weight percentages (wt%) of the aluminum alloy obtained are Cu: 1.2, Mg: 2.1, Zn: 8.1, TiB 2 : 2%; the total content of other impurity elements is ≤0.05%, and the balance is Al.

[0086] Comparative Example 1

[0087] Pure Al, Al-Cu alloy, zinc ingot, magnesium ingot and Al 2 O 3 The raw material is cast in a conventional crucible melting furnace, fully stirred with a graphite stirrer, and the prepared cast rod is remelted at 750°C. The homogenization system is 390°C×3h+440°C×12h+465°C×24h, the extrusion die temperature is 420°C, the aluminum alloy cast rod heating temperature is 435°C, the solid solution system is 460°C×70min, the insulation aging is 150°C×10h+100°C×10h, and water cooling. The components and their weight percentages (wt%) of the obtained aluminum alloy are Cu: 2.8, Mg: 3.8, Zn: 5.1; the total content of other impurity elements is ≤0.05%, and the balance is Al.

[0088] Comparative Example 2

[0089] Pure Al, Al-Cu alloy, zinc ingot, magnesium ingot, KBF 4 , K 2 TiF 6 and Al 2 O 3 As raw materials, cast in a conventional crucible melting furnace, fully stirred with a graphite stirrer, remelted at 750°C, homogenized at 390°C × 3h + 440°C × 12h + 465°C × 24h, extrusion die temperature at 420°C, aluminum alloy casting heating temperature at 435°C, solution system at 460°C × 70min, insulation aging at 150°C × 10h + 100°C × 10h, water cooling. The components and weight percentages (wt%) of the aluminum alloy are Cu: 2.8, Mg: 3.8, Zn: 5.1, TiB 2 : 2.2%; the total content of other impurity elements is ≤0.05%, and the balance is Al.

[0090] Comparative Example 3

[0091] Pure Al, Al-Cu alloy, zinc ingot, magnesium ingot and Al 2 O 3 The raw material is cast in a conventional crucible melting furnace, fully stirred with a graphite stirrer, and the prepared cast rod is remelted at 750°C. The homogenization system is 390°C×3h+440°C×12h+465°C×24h, the extrusion die temperature is 420°C, the aluminum alloy cast rod heating temperature is 435°C, the solid solution system is 460°C×70min, the insulation aging is 150°C×10h+100°C×10h, and water cooling. The components and their weight percentages (wt%) of the obtained aluminum alloy are Cu: 1.2, Mg: 2.1, Zn: 8.1; the total content of other impurity elements is ≤0.05%, and the balance is Al.

[0092] Comparative Example 4

[0093] Pure Al, Al-Cu alloy, zinc ingot, magnesium ingot, KBF 4 , K 2 TiF 6 and Al 2 O 3 The raw material is cast in a conventional crucible melting furnace, fully stirred with a graphite stirrer, and the prepared cast rod is remelted at 750°C. The homogenization system is 460°C×48h, the extrusion die temperature is 420°C, the aluminum alloy cast rod heating temperature is 435°C, the solid solution system is 460°C×70min, the insulation aging is 150°C×10h+100°C×10h, and water cooling. The components and their weight percentages (wt%) of the obtained aluminum alloy are Cu: 1.2, Mg: 2.1, Zn: 8.1, TiB 2: 2%; the total content of other impurity elements is ≤0.05%, and the balance is Al.

[0094] Comparative Example 5

[0095] Pure Al, Al-Cu alloy, zinc ingot, magnesium ingot, KBF 4 , K 2 TiF 6 and Al 2 O 3 As raw materials, cast in a conventional crucible melting furnace, fully stirred with a graphite stirrer, homogenized at 390°C × 3h + 440°C × 12h + 465°C × 24h, extrusion die temperature at 420°C, aluminum alloy rod heating temperature at 435°C, solution system at 460°C × 70min, insulation aging at 150°C × 10h + 100°C × 10h, water cooling. The components and their weight percentages (wt%) of the obtained aluminum alloy are Cu: 1.2, Mg: 2.1, Zn: 8.1, TiB 2 : 2%; the total content of other impurity elements is ≤0.05%, and the balance is Al.

[0096] Comparative Example 6

[0097] Pure Al, Al-Cu alloy, zinc ingot, magnesium ingot, KBF 4 , K 2 TiF 6 and Al 2 O 3 As raw materials, cast in a conventional crucible melting furnace, fully stirred with a graphite stirrer, and the prepared cast rods were remelted again at 750°C, the homogenization system was 390°C×3h+440°C×12h+465°C×24h, the extrusion die temperature was 420°C, the aluminum alloy cast rod heating temperature was 435°C, the solid solution system was 460°C×70min, the insulation aging was 150°C×10h+100°C×10h, and water-cooled. The components and their weight percentages (wt%) of the obtained aluminum alloy are Cu: 1.2, Mg: 2.1, Zn: 8.1, TiB 2 : 2%; the total content of other impurity elements is ≤0.05%, and the balance is Al.

[0098] Comparative Example 7

[0099] Pure Al, Al-Cu alloy, zinc ingot, magnesium ingot, KBF 4 , K 2 TiF 6 and Al 2 O 3As raw materials, cast in a conventional crucible melting furnace, fully stirred with a graphite stirrer, remelted at 750°C, homogenized at 390°C × 3h + 440°C × 12h + 465°C × 24h, extrusion die temperature at 420°C, aluminum alloy casting heating temperature at 435°C, solution system at 460°C × 70min, aging at 150°C × 10h + 100°C × 10h, water cooling. The components and weight percentages (wt%) of the aluminum alloy obtained are Cu: 1.1, Mg: 2, Zn: 8.2, TiB 2 : 2%; the total content of other impurity elements is ≤0.05%, and the balance is Al.

[0100] Comparative Example 8

[0101] Pure Al, Al-Cu alloy, zinc ingot, magnesium ingot, KBF 4 , K 2 TiF 6 and Al 2 O 3 As raw materials, cast in a conventional crucible melting furnace, fully stirred with a graphite stirrer, and remelted at 750°C. The homogenization system is 390°C×3h+440°C×12h+465°C×24h, the extrusion die temperature is 420°C, the aluminum alloy casting temperature is 435°C, the solid solution system is 460°C×70min, the insulation aging is 150°C×10h+100°C×10h, and water cooling. The components and their weight percentages (wt%) of the obtained aluminum alloy are Cu: 2.9, Mg: 3.9, Zn: 8.2, TiB 2 : 2%; the total content of other impurity elements is ≤0.05%, and the balance is Al.

[0102] Table 1 shows the performance results of the aluminum alloys obtained in the examples and comparative examples.

[0103] Table 1

[0104]

[0105] By comparing the examples with the comparative examples, it can be seen that, compared with Example 8, in Comparative Example 4, under the single-stage homogenization system, the tensile strength and yield strength of the alloy show a downward trend; under the three-stage homogenization system, the strength of the alloy is significantly improved, and the elongation after fracture is slightly reduced. This shows that under the three-stage homogenization system, the strength of the material can be effectively improved. This is because low-temperature homogenization can fully diffuse, nucleate and grow the microalloying elements, so that the dispersed phase inside the crystal is precipitated, and finally after the three-stage homogenization treatment, the alloying elements can be diffused and dissolved into the matrix.

[0106] Compared with Comparative Examples 5 and 6, the aluminum-based composite material that was not remelted but stirred with a conventional graphite stirrer had the lowest mechanical properties and a large amount of undissolved phase appeared, as shown in the attached manual. Figure 3 As shown in the figure, after the first remelting, the mechanical properties are significantly improved, and after the second remelting, the properties tend to decrease compared with the first remelting. Figure 2 As shown in the figure, after the first remelting, the aggregation degree of the cast rod is reduced, no large undissolved phase appears, and the residual molten salt in the melt is discharged, so that the mechanical properties of the alloy after extrusion are improved. Figure 4 As shown in the figure, the performance degradation is due to the secondary melting, which causes burning of some alloys and reduces the alloying composition, resulting in reduced performance after extrusion.

[0107] Compared with Comparative Examples 7 and 8, although the Zn content of Examples 7 and 8 is increased, so that their yield strength and tensile strength are improved, their elastic modulus is low and cannot meet the requirements.

[0108] Compared with Comparative Example 2 and Comparative Example 3, Examples 1-4 show that as TiB 2 The increase of TiB content significantly improves the mechanical properties. 2 The addition of can change the substructure, dislocation configuration, grain size and material density of the material, thus improving the performance. 2 When the content is between 0.5% and 1.5%, the performance tends to be stable; when TiB 2 When the content is 2%, the performance is the highest; when the content is 2.2%, the performance tends to decrease. 2 The addition of can improve the elastic modulus of the material. This is because the nanoparticles themselves have a high elastic modulus, which will seriously hinder the movement of dislocations during deformation, resulting in an increase in dislocation density, which is of great significance for improving the strength of Al-Zn-Mg-Cu alloys.

[0109] TiB 2 The addition of TiB has a certain influence on the evolution of the deformation structure of Al-Zn-Mg-Cu alloy after extrusion and heat treatment, the size and distribution of nano-precipitates. 2 The addition of MgZn leads to the refinement of deformed grains, more dislocations in the alloy structure, and the dislocation strengthening mechanism caused by dislocation entanglement and precipitated phase (MgZn 2 ) is more evenly distributed, which improves the strength of the alloy.

[0110] The high temperature performance of Example 4, Comparative Example 1 and Comparative Example 2 was tested, and the results are shown in Table 2

[0111]

[0112] It can be seen from Example 4, Comparative Example 1 and Comparative Example 2 that an appropriate amount of TiB 2 It can improve the high temperature performance of aluminum alloy. Excessive TiB 2 The low mechanical properties lead to a decrease in high temperature performance, which is not conducive to the improvement of high temperature performance.

[0113] Comparison of Examples 1-8 with Comparative Examples 7 and 8 shows that the aluminum alloy having the specific weight ratio of the alloy components and the reinforcing phase provided by the present invention and prepared by the method provided by the present invention has more excellent comprehensive properties.

[0114] As the instruction manual Figure 5 , 6 As shown in the figure, they are SEM schematic diagrams of the extruded profiles of Example 4 and Comparative Example 2, respectively. It can be seen that a large number of gray second phases are aggregated in the alloy. The gray part in Example 4 is less than that in Comparative Example 2, indicating that the high content of TiB 2 The occurrence of clustering phenomenon increases, which will cause the performance of the alloy to deteriorate.

[0115] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An aluminum alloy, characterized in that: The components and their weight percentages in the aluminum alloy are: Cu content is 1.2-2.8%; Mg content is 2.1-3.8%; Zn content is 5.1-8.1%; TiB2 content is 0.5-2%; The total content of other impurity elements is ≤0.05%; The balance is Al.

2. The aluminum alloy according to claim 1, characterized in that The components and their weight percentages in the aluminum alloy are: Cu content is 1.2-2%; Mg content is 2.1-2.9%; Zn content is 5.1-6.1%; TiB2 content is 0.5%-2%; The total content of other impurity elements is ≤0.05%; The balance is Al.

3. A method for preparing the aluminum alloy according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: The aluminum alloy raw material is placed in a crucible for melting and casting, and stirred with a stirrer for 5-10 minutes. The obtained cast rod is remelted at 720-740°C, refined, slag-stripped, and cast; The aluminum alloy ingot after one remelting and casting is subjected to homogenization heat treatment, and the homogenization system adopts (380-400℃)×3h+(410-440℃)×(8-16h)+(450-480℃)×(20-28h); The aluminum alloy ingot after homogenization heat treatment is extruded, the extrusion die temperature is 410-430°C, the aluminum alloy casting rod heating temperature is 425-440°C, and the extrusion speed is 0.5-1m / min; The extruded aluminum alloy bar is subjected to a solid solution treatment at a temperature of 455-465°C × (60-100) min; The aluminum alloy rod after solid solution is subjected to thermal insulation aging, adopting a double-stage aging system, (140-160℃)×(8-12h)+(80-120℃)×(8-12h), and water cooling.

4. The preparation method according to claim 3, characterized in that: The aluminum alloy raw materials include pure Al, Al-Cu alloy, zinc ingot, magnesium ingot, KBF4 and K2TiF6.

5. The preparation method according to claim 3, characterized in that: The smelting and casting step comprises the following steps: Put pure Al, Al-Cu alloy and zinc ingot into a graphite crucible, place it in a resistance furnace at 850℃ and heat it until it is melted; after melting, when the temperature is ≥730℃, add magnesium ingot; wait until the intermediate alloy is completely melted and stir it thoroughly; add mixed salt, stir it thoroughly with a graphite stirrer, remove the slag, add Al2O3, dilute the reaction water, and keep it warm for 10 minutes; after keeping warm, add a certain amount of pure Al.

6. The preparation method according to claim 3, characterized in that: The KBF4 and K2TiF6 are reacted in situ to produce TiB2; Among them, the in-situ reaction temperature is (850±3)℃.

7. Use of the aluminum alloy according to claim 1 or 2, or the aluminum alloy prepared by the preparation method according to any one of claims 3 to 6 in the automotive field.